A method of red-eye effect recognition in digital photography - Agayan, A.V.; Agayan, G.M.; Romanov, S.Yu. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2005)
The paper is devoted to the red-eye effect recognition on digital photos made with flash. RGB digital photos were used as input data. The recognition algorithm consists of three steps: preliminary, finite parametric filtration, and context filtration. After that the recognition correction is performed. The algorithm was tested on a wide range of different-quality photos. The best recognition was achieved on the photos with large areas of pupils.